Illness Perceptions, Coping Strategies, and Quality of Life in People With Multiple Chronic Conditions. Issue 2 (3rd February 2020) - Cheng, Cheng; Yang, Cong‐Yan; Inder, Kerry; Chan, Sally Wai-Chi
Abstract: Purpose: To determine whether illness perceptions, coping strategies, and sociodemographic and clinical variables are related to the quality of life (QoL) in adults with multiple chronic conditions (MCCs) living in China. Design: By employing a cross‐sectional design based on the transactional stress and coping theory, a convenience sample of adults with MCCs were recruited from a university‐affiliated hospital between November 2017 and May 2018 in Northern Anhui, China. Methods: A self‐reported questionnaire, including the Brief Illness Perceptions Questionnaire, the Brief Coping Orientation to Problems Experienced inventory, and the Short Form Survey version 2, was administered. Sociodemographic and clinical data regarding MCCs were also collected. Descriptive statistics including frequencies, means, standard deviations, and correlation coefficients were calculated to examine the relationship between illness perceptions, coping, and QoL. Hierarchical multiple regression models were used to identify variables associated with physical and mental QoL. Findings: A total of 351 participants (50% male) were recruited, with a mean age of 58.9 years ( SD = 14.6). Of the participants, 83% had two chronic conditions. Participants reported impaired physical and mental QoL when compared with the general population in China. Poorer QoL was correlated with stronger illness perceptions of consequences and timeline and increased use of denial and disengagement and self‐blame. Increasing age and more chronic conditions were associated with worse QoL. A higher education level was significantly associated with better physical and mental QoL. Conclusions: This study found that adults with MCCs living in China experienced impaired QoL. The strong relationship found between the participants' perceptions of MCCs, coping strategies, and QoL suggested that healthcare professionals should recognize the physical and psychological impacts of MCCs and address the significance of adaptations to MCCs in future treatment programs. The findings will help healthcare professionals design more specific interventions to modify illness perceptions and enhance certain coping strategies to improve the QoL of people with MCCs. Healthcare professionals can mobilize available resources from healthcare and social systems to enhance people's coping and adaptation to MCCs. Clinical Relevance: With an understanding of the illness perceptions of people with MCCs, healthcare professionals could offer information related to consequences, timeline, and personal control to enable better alignment between people's expectations and their actual situations. By knowing people's coping strategies, healthcare professionals can offer additional support to people who prefer strategies of denial and disengagement and self‐blame.